2011
DOI: 10.1007/s00432-011-1102-1
|View full text |Cite
|
Sign up to set email alerts
|

ARK5 is associated with the invasive and metastatic potential of human breast cancer cells

Abstract: ARK5 led to a more invasive phenotype and metastatic potential in human breast cancer dependent on Akt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 19 publications
0
42
0
2
Order By: Relevance
“…It has three binding sites for miR-211 in its 3 0 UTR (Figure 4a). Functional studies revealed its involvement in induction of senescence (Humbert et al, 2010), regulation of proliferation through p53 phosphorylation (Hou et al, 2011), promotion of cell survival (Suzuki et al, 2003), invasion and metastasis Chang et al, 2012), and loss of cellular adhesion (Zagorska et al, 2010). Although NUAK1 is overexpressed in several cancers (Chang et al, 2012), little is known about its role in melanoma.…”
Section: Mir-211 Modulates Adhesion Ability Of Melanomasmentioning
confidence: 99%
“…It has three binding sites for miR-211 in its 3 0 UTR (Figure 4a). Functional studies revealed its involvement in induction of senescence (Humbert et al, 2010), regulation of proliferation through p53 phosphorylation (Hou et al, 2011), promotion of cell survival (Suzuki et al, 2003), invasion and metastasis Chang et al, 2012), and loss of cellular adhesion (Zagorska et al, 2010). Although NUAK1 is overexpressed in several cancers (Chang et al, 2012), little is known about its role in melanoma.…”
Section: Mir-211 Modulates Adhesion Ability Of Melanomasmentioning
confidence: 99%
“…It suppresses cell death induced by nutrient starvation and activation of death receptors through inhibition of caspase 8, and the negative regulation of procaspase 6 (8,9). ARK5 is also strongly associated with tumor invasion and metastasis, and is a tumor survival and tumor progression factor (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…NUAK1 has been shown to promote glioma cell invasion, and its elevated expression correlates with a poor clinical outcome (17). NUAK1 has also been shown to be associated with a more invasive phenotype and metastatic potential in human breast cancer dependent on Akt (18). In addition, the overexpression of NUAK1 is associated with a poor prognosis in hepatocellular carcinoma (19).…”
Section: Introductionmentioning
confidence: 99%